Greta Thunberg’s biography Against climate change and the pandêmica: the educational and alarmista profiles - Almeida, Simão Farias (Revista Letras Raras, 2021)
Since 2018, coverage on news websites of the discourse and actions of the Swedish schoolgirl Greta Thunberg has tended to provide visibility to her personal profiles of engagement and coherence, and her educational and alarmist social profiles, with regard to climate change. This article uses Ecocriticism (GARRARD, 2006), environmental journalism (BOYKOFF, 2011) and the biographical method of investigating the phenomenological field of the subject and understanding the extent of her experiences and her significance (VILAS-BOAS, 2008), in order to demonstrate the manner in which these profiles of the activist have been constructed in four journalistic articles from the websites: France Presse, G1 (Grupo Globo de Comunicação), Deutsche Welle Brasil and BBC News Brasil. The intention is to investigate whether this biography transverses a planetary mindset and an interdependent ecological awareness of solidarity against the global crisis of the earth’s ecosystem and the Covid-19 pandemic, characteristics of future education and communication according to Morin (2003). The article concludes that Greta Thunberg is skeptical in relation to the apathy of governments and is authentic in her defense of climate causes, thereby decimating false inconsistencies between her educational and alarmist roles so as to criticize and change planetary mindsets.